Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914 - Thwaites, James (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914," by James A. Schmiechen.